2014
DOI: 10.1161/circresaha.115.303632
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-Specific YAP Activation Improves Cardiac Function and Survival in an Experimental Murine MI Model

Abstract: Rationale Yes-Associated Protein (YAP), the terminal effector of the Hippo signaling pathway, is crucial for regulating embryonic cardiomyocyte (CM) proliferation. Objective We hypothesized that YAP activation after myocardial infarction would preserve cardiac function and improve survival. Methods and Results We used a cardiac-specific, inducible expression system to activate YAP in adult mouse heart. Activation of YAP in adult heart promoted CM proliferation and did not deleteriously affect heart functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
321
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 357 publications
(339 citation statements)
references
References 35 publications
13
321
4
1
Order By: Relevance
“…A second group (Polizzotti et al, 2015) further showed that administration of neuregulin 1 in neonatal mouse hearts or cardiomyocytes derived from paediatric patients also brings beneficial effects to myocardial function through cardioprotection ( protection from cell death) and proliferation. Nevertheless, none of these experiments has demonstrated a lack of scarring in the adult heart, which is important since the activity of the fibroblast cells also needs to be addressed in order to achieve full regeneration (D'Uva et al, 2015;Lin et al, 2014;Polizzotti et al, 2015;Xin et al, 2013).…”
Section: Modulation Of Cardiomyocyte Activitymentioning
confidence: 99%
“…A second group (Polizzotti et al, 2015) further showed that administration of neuregulin 1 in neonatal mouse hearts or cardiomyocytes derived from paediatric patients also brings beneficial effects to myocardial function through cardioprotection ( protection from cell death) and proliferation. Nevertheless, none of these experiments has demonstrated a lack of scarring in the adult heart, which is important since the activity of the fibroblast cells also needs to be addressed in order to achieve full regeneration (D'Uva et al, 2015;Lin et al, 2014;Polizzotti et al, 2015;Xin et al, 2013).…”
Section: Modulation Of Cardiomyocyte Activitymentioning
confidence: 99%
“…Therefore, we generated the adeno-associated virus 9:cTNT::Fgf16 virus (AAV9:Fgf16), in which expression of Fgf16 was driven by the cardiomyocytespecific cTNT promoter and the plasmid was packaged into AAV9, a virus that targets cardiomyocytes efficiently and specifically (Lin et al, 2014). We first used AAV9:cTNT::GFP-Cre (AAV9:GFPCre) to evaluate the transduction efficiency and specificity in the Rosa26 RFP/+ reporter mouse.…”
Section: Gata4 Is Required For Coronary Angiogenesis During Neonatalmentioning
confidence: 99%
“…AAV9 were packaged in 293T cells with AAV9:Rep/Cap and pAd:deltaF6 ( pHelper) as described previously (Grieger et al, 2006;Lin et al, 2014). AAV9 were then purified and concentrated by gradient centrifugation.…”
Section: Aav9 Packaging and Deliverymentioning
confidence: 99%
“…10 Third, Yap promotes activation of Akt, a serine/threonine kinase that promotes cell survival, through unknown mechanisms stimulating PI3K. 4, 9 The importance of each mechanism may differ depending upon the type of stress.…”
Section: Hippo Pathway In Heart Developmentmentioning
confidence: 99%